1984
DOI: 10.1002/1097-4679(198405)40:3<788::aid-jclp2270400326>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Wechsler adult intelligence scale and wechsler adult intelligence scale-revised in a neurologically impaired population

Abstract: Compared Verbal, Performance, and Full Scale IQ scores from two groups of neurologically impaired patients (N = 114) similar in age, years of education, occupation, race, sex, and etiology and location of cerebral dysfunction. One group had been given the WAIS and the other the WAIS‐R. All three IQ scores were higher for the WAIS group, with Full Scale and Verbal scores significantly (p < 0.05) higher. Changes in item content and standardization sample cohort effects are offered as partial possible explanation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
11
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…The two scales were found to yield analogous results at all neurological impairment levels. Kelly, Montgomery, Felleman, and Webb, 1984 matched two groups of neurologically impaired patients for age, years of education, gender, race, occupation, and etiology and location of cerebral dysfunction. One group was given the WAIS, and the other group was given the WAIS-R.…”
Section: Comparisons Between the Wais And The Wais-rmentioning
confidence: 99%
“…The two scales were found to yield analogous results at all neurological impairment levels. Kelly, Montgomery, Felleman, and Webb, 1984 matched two groups of neurologically impaired patients for age, years of education, gender, race, occupation, and etiology and location of cerebral dysfunction. One group was given the WAIS, and the other group was given the WAIS-R.…”
Section: Comparisons Between the Wais And The Wais-rmentioning
confidence: 99%
“…Wechsler's IQ tests have been the most widely used measures of intelligence in neuropsychological settings (Lees-Haley, Smith, Williams, & Dunn, 1996). Sound psychometric properties, breadth of content, a wealth of neuropsychological data, and the availability of age-based normative data all contribute to its widespread use (Kelly, Montgomery, Felleman, & Webb, 1984). The Wechsler–Bellevue Intelligence Scale (Wechsler, 1939) was followed by the Wechsler Adult Intelligence Scale (WAIS; Wechsler, 1955), the WAIS–Revised (Wechsler, 1981), and, most recently, the WAIS–III (Tulsky, Zhu, & Ledbetter, 1997).…”
Section: Part 1: the Aging Of Testsmentioning
confidence: 99%
“…Since the publication of the revised form of the WAIS in 1981, several studies have explored the comparability of the 1955 and the 1981 versions of this instrument (Chelune, Eversole, Kane, & Talbott, 1987;Edwards & Klein, 1984;Kelly, Montgomery, Felleman, & Webb, 1984;Lippold & Claiborn, 1983;Mishra & Brown, 1983;Smith, 1983). Most of these investigations have found differences in IQ scores obtained by subjects administered both tests, with WAIS IQ scores tending to average approximately 7 to 8 points higher than WAIS-R IQ scores.…”
mentioning
confidence: 92%
“…The finding of higher WAIS scores has led to considerable speculation about the reasons underlying the discrepancies in scores. The two most often-stated hypotheses are (1) that differences exist in the test items such that the WAIS-R is more difficult; and (2) that the standardization samples for the two tests differ along important dimensions such as education, nutritional status, or occupational status (Anastasi, 1982;Kelly et al, 1984) or perhaps along dimensions that have not yet been identified (Flynn, 1984(Flynn, ,1987.…”
mentioning
confidence: 99%